2017
DOI: 10.1159/000481213
|View full text |Cite
|
Sign up to set email alerts
|

FCGR2A and FCGR3A Genotypes Correlate with Farletuzumab Response in Patients with First-Relapsed Ovarian Cancer Exhibiting Low CA125

Abstract: Farletuzumab is a humanized monoclonal antibody that binds to folate receptor alpha and elicits an anti-tumor response via immune effector activity. Recent studies from a global phase 3 trial in ovarian cancer patients treated with carboplatin/taxane plus farletuzumab found that the tumor-produced CA125 protein can suppress farletuzumab function via perturbing its engagement to the activating Fc-γ receptors CD32a (FCGR2A) and CD16a (FCGR3A). Previous reports have indicated that naturally occurring polymorphism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…Of the commercial IgG1‐type antibodies, rituximab showed significant inhibition of C1q binding in the presence of CA125, while pertuzumab did not. Previous studies have shown that CA125 does not bind pertuzumab nor does it affect its ability to engage with CD16a, therefore further supporting the finding that CA125 direct antibody binding perturbs the ability of C1q engagement and subsequent CDC activity . Daudi cells have been reported to be susceptible to the CDC‐mediated killing by rituximab in vitro .…”
Section: Resultssupporting
confidence: 61%
See 4 more Smart Citations
“…Of the commercial IgG1‐type antibodies, rituximab showed significant inhibition of C1q binding in the presence of CA125, while pertuzumab did not. Previous studies have shown that CA125 does not bind pertuzumab nor does it affect its ability to engage with CD16a, therefore further supporting the finding that CA125 direct antibody binding perturbs the ability of C1q engagement and subsequent CDC activity . Daudi cells have been reported to be susceptible to the CDC‐mediated killing by rituximab in vitro .…”
Section: Resultssupporting
confidence: 61%
“…In light of our observed farletuzumab‐mediated CDC suppression and the previous reports that CA125 can affect ADCC by direct antibody binding , we determined if other circulating antibodies were capable of binding CA125. First, total purified human IgM and IgG1 from serum of healthy volunteers were tested for their ability to bind CA125.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations